Analisa Faktor-Faktor yang Mempengaruhi Keterlambatan Pembayaran pada Manajemen Keuangan BMT Muamalah Syariah Tebuireng - Lailatul Maghfiroh Putri Rifardi; Susi Noviana; Indah Raissa Qurani; Peni Haryanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study analyzes the factors that influence late payments in the financial management of BMT Muamalah Syariah Tebuireng. Late payments can be caused by various complex factors in the context of sharia financial management. According to the literature, several main factors that can influence late payments include a lack of understanding and awareness of the obligation to pay on time, economic instability which causes low liquidity, and less effective risk management. In addition, internal factors such as complex internal processes and lack of coordination between units within BMT can also contribute to payment delays. Observations of practices at BMT Muamalah Syariah Tebuireng show that although sharia principles are emphasized, challenges such as compliance with administrative procedures and regulations are often factors that slow down payments. By understanding these factors through literature studies and observations, more effective strategies in financial management can be identified to reduce late payments in the context of BMT Muamalah Syariah Tebuireng.